Concelho de Mafra: 180 anos de bandas filarmónicas - uma exposição - Soares, Ana Catarina Ribeiro e Silva Ehrhardt (2021)
This Master´s Project Work in Museology and Museography, is the creation of an exhibition and due course, based in three interconnected thematic nuclei that have as one of main objectives, to make know to the reader of this work and to a future public some of the objects that belong to the spoils of three of the six philharmonic bands of Mafra County, and through them, alert people to the need to preserve them so that they do not disappear and be enjoyed by future generations. In order to better understand which objects would be more relevant to the exhibit, I began by surveying the stories of these bands, which allowed me to understand the paths since the dates of their foundations and thus determine that there were some objects linked to moments and remarkable dates – along with some that I knew were indispensable to present – that would be important in helping to better understand the idea that is intended to be conveyed with this work. Later I began to select from a series of object those that would effectively integrate the project, and to think about the most logical way to group them, thus reaching the three thematic nuclei that constitute the division between the photographs, uniforms and banners that are part of the first core, and introduce the people who make up the bands, in the second core, we will have some scores and instruments that focus on the work done, and the tools need it to do it, and finally we will have the pennants, trophies, among others that show us a part of the result of all the work these bands do. In addition to mounting the exhibition, we will also have a characterization of the municipality of Mafra, which allow us to understand the sociocultural context in which these bands were evolving until today.